Identifying Occupation Groups for Suicide Prevention: A Statewide Data Linkage Study. Issue 2 (3rd April 2023) - Henn, Morissa; Barber, Catherine; Zhang, Wilson; Staley, Michael; Azrael, Deborah; Miller, Matthew
Abstract: Objective: To identify suicide rates by occupation category in Utah and describe the hospital history and circumstances of suicide decedents in the occupation category that had the state's highest rate and highest number of suicides: Construction and Extraction. Method: We used data on suicide decedents from the National Violent Death Reporting System (NVDRS) for 2005–2015 ( n = 4, 590) to calculate sex- and occupation-specific suicide rates among adults 18–65 years old in Utah. For working-age men who died by suicide during the years 2014–2015 ( n = 623), we linked NVDRS data with decedents' hospital histories. Results: One in five working-age men who took their life in Utah worked in Construction and Extraction, the single Bureau of Labor Statistics occupation category with both the highest number ( n = 719) and rate of suicides (86.4/100, 000 men vs. a range of 15.3–66.2 for other occupations). For females, there was no occupation group that had both high rates of suicide and high numbers of suicides compared with other occupations, so there was no clear occupation group to focus on in the same way there was for men. Using linked data for 2014–2015 deaths, 58% of men in Construction and Extraction who died by suicide had been diagnosed in the hospital in the past three years with a substance abuse or mental health problem, and a quarter (25%) tested positive for opioids on post-mortem examination. Nearly half (48%) of 2014–2015 male suicide decedents in Construction and Extraction were reported to have intimate partner problems, about a quarter (26%) had a criminal problem, a quarter (25%) were unemployed, and over half (54%) died by gunshot. Conclusions: Linked data identified Construction and Extraction as a potentially high-impact occupation group for suicide prevention and suggested potential contexts for intervention. HIGHLIGHTS: Construction and Extraction stands out as an occupation group with a very high number and rate of suicides. Two-thirds of male decedents in Construction and Extraction had a substance abuse problem. For Utah females, there were no occupations with both high rates and high numbers of suicides.